Hubungan Pengetahuan dan Self Efficacy dengan Kepatuhan dalam Pembatasan Cairan Pada Pasien Chronic Kidney Desease (CKD) - Arif, Muhammad; Hasanah, Intan Hikmatul; Murni, Lilisa (Jurnal Keperawatan Medika, 2024)
Chronic Kidney Disease (CKD) is ranked 10th as the top 10 causes of death in the world. Where there has been a case of CKD at Dr. Achmad Mochtar Bukittinggi Hospital in the medical ward, and the CKD patient does not comply with fluid restrictions, it will experience fluid buildup so that it can cause edema. However, this non-compliance is due to a lack of knowledge and self-efficacy so that the ability of patients to control the fluids they consume is reduced. This study aims to determine the relationship between knowledge and self-efficacy with compliance in fluid restriction in Chronic Kidney Desease (CKD) patients in the medical ward of Dr. Achmad Mochtar Bukittinggi Hospital in 2023. This research method was descriptive correlation with cross sectional type of research using chi-square test. The sample in this study amounted to 42 respondents using accidental sampling technique. This research instrument uses a questionnaire. The results showed that respondents with good knowledge had compliance with the obedient category as many as 19 (76.0%) with a p-value = 0.050 (p <0.1) there was a relationship between knowledge and compliance in fluid restriction in CKD patients. Respondents with low self efficacy have compliance with the non-adherent category as many as 12 (48.0%) with a p-value = 0.201 (p>0.1) there is no relationship between self efficacy and compliance in fluid restriction in CKD patients. The conclusion of the results of this study is that there is a significant relationship between knowledge and compliance in fluid restriction in CKD patients, and there is no significant relationship between self efficacy and compliance in fluid restriction in CKD patients. It is hoped that patients can increase self efficacy and get motivational support from family / friends in order to increase compliance with fluid restriction in CKD patients.